GRANULATION OF POWDER MATERIALS WHEN USING «FATTENING» TECHNOLOGY - R. V. Morozov; Yu. A. Taran; A. L. Taran (Тонкие химические технологии)
In this paper we considered the granules formation process using the "fattening" technology in a granulation bowl. Development of rolling overgranulation technology primarily due to the need to obtain granules of larger size with much better quality indicators than those that can be attained in granular towers. Also, this technology gives granules with a complex chemical composition. Fattening is the process of overgranulation of an initial pellet by powder (with or without binding) by rolling in different devices, including bowls. The mathematical description of various embodiments of the process: with or without the birth of pellets. Besides, the process of fragmentation of the granules is considered separately. Fragmentation is usually an undesirable process, but sometimes it is not possible to get rid of it. The calculation results obtained by the models are represented as a series of graphic dependencies. We also develop algorithms that allow for the effect of fragmentation and agglomeration in arbitrary ratios. A block diagram of the implementation of the algorithm is also presented in the paper.